#TITLE_ALTERNATIVE# - Tonapa Sarungu, Yunus
Abstract : Microbiological corrosion as one of numerous material damage can occur in an environment containing the bacteria of Desulfivi6rio Desulfuricans type, which is usually called Sulfate Reducing Bacteria ( SRS ), since it can reduce the S04<sup2- ion to S2- ion. The Natrium- Benzoat has been largely recognized as a food preservative which is able to kill the bacteria as the inhibitor against the steel corrosion. In this research the effectivenes of the Na - bonnet as the inhibitor of the microbiological corrosion in the mild steel is tested by comparing the rate of the steel corrosion in groundwater environment planted with SRB and wihtout addition of inhibitor. The measurement of corrosion rate is conducted using the weight losses method. Based on the experiment result it can bi concluded that the mild steel in groundwater containing SRB is corroded in accordance with the mechanism proposed by M. Stepheson and J.M. Sharply assisted by the ferobacteria and producing the FeS as the result of corrosion. The carbon steel sample in groundwater is the place where the numerous bacteria grow, including the bacteria S2' that oxidises into S042- , as a result SRB can grow and flourish rendering the groundwater more corrosive. The addition of Na- benzoat until 10 ppm can only inhibit the growth of the bacteria and reduce the rate of corrosion a little bit. The possible safety limit of the corrosion rate can be reached with the number of inhibitor ? 1000 ppm. The use of Na- benzoat will be more effective if added periodically.